2001
DOI: 10.2109/jcersj.109.1271_602
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Single Crystalline and Polycrystalline Silicon Carbides Evaluated by Vickers Indentation.

Abstract: Fracture toughness, fracture surface energy and crack initiation load of single crystal and polycrystalline SiC sintered with different additives were evaluated by Vickers indentation technique. Resistance to crack initiation and propagation in sintered SiC with Al2O3 additive was>sintered SiC with B and C additives> single crystals. The properties of single crystals depended on crystal orientation, while little difference of properties was observed between 4H and 6H structures. High fracture toughness and fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…14,15 Shockley partial dislocations bordering intrinsic stacking faults are thought to be most relevant in hexagonal SiC, 5,16 with mobility of leading partials exceeding that of trailing partials at low temperatures, 17 supporting a tendency for plasticity to be accompanied by generation of large numbers of stacking faults. 20 The present work addresses nonlinear behavior of single crystals of 6H-SiC. 18͒ does not appear to be an important mechanism in hexagonal polytypes, except at high temperatures and pressures wherein phase transformations occur.…”
Section: Introductionmentioning
confidence: 97%
“…14,15 Shockley partial dislocations bordering intrinsic stacking faults are thought to be most relevant in hexagonal SiC, 5,16 with mobility of leading partials exceeding that of trailing partials at low temperatures, 17 supporting a tendency for plasticity to be accompanied by generation of large numbers of stacking faults. 20 The present work addresses nonlinear behavior of single crystals of 6H-SiC. 18͒ does not appear to be an important mechanism in hexagonal polytypes, except at high temperatures and pressures wherein phase transformations occur.…”
Section: Introductionmentioning
confidence: 97%
“…It has been long suggested that silicon carbide (SiC) would be a competitor material to ULE and Zerodur for building the next-generation large-scale reflecting mirrors, particularly used in the space-based telescope, owing to its high stiffness-to-density ratio and low thermal distortion properties [5][6][7]. However, SiC is a typical difficult-to-machine material because of its extreme hardness, only lower than diamond, cubic boron nitride (cBN), and boron carbide (B 4 C) [8]. The extreme hardness induced an extremely low material removal rate.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of SiC single crystals depended on the crystal planes. 14) Development of texture in SiC by hot forging 15) and the Templated Grain Growth method 16) has been reported. On the other hand, the crystallographic orientation even in feeble magnetic ceramics, such as Al 2 O 3 and AlN, etc., can be controlled by a colloidal processing under a magnetic field.…”
Section: Introductionmentioning
confidence: 99%